Mi abuela y yo - Mayer, Mercer, 1943- (Racine, Wis. : Western Pub. Co., 1994)
A trip to the beach with Grandma provides lots of fun and surprises.
Translation of: Just grandma and me.
Keywords: Grandmothers -- Juvenile fiction; Beaches -- Juvenile fiction; Fiction